Perspective on global development 2010 - Shifting wealth (Paris, 2010)
"The 2010 Perspectives on Global Development: Shifting Wealth looks at the major realignment of the global economy that has taken place in the last two decades. Economic and political power has been shifting towards the developing world and emerging economies thanks to high and sustained growth rates in large developing countries, particularly the Asian giants of China and India. Increasing links between developing countries has been a feature of this transformation: flows of trade, aid and investment between developing countries have all intensified. Which countries have had the most rapid growth? How does the rise of the Asian giants affect the global economy and the rest of the developing world? And how can poor countries take advantage of the new economic landscape? Answers and insights in this edition."